Immune Regulation of TNFAIP3 in Psoriasis through Its Association with Th1 and Th17 Cell Differentiation and p38 Activation - Yanyun Jiang; Wenming Wang; Xiaofeng Zheng; Hongzhong Jin (Journal of Immunology Research)
Background. Psoriasis is an immune-mediated chronic inflammatory skin disorder in which the dysregulation of immune cells plays an important role in its development. Tumor necrosis factor- (TNF-) α antagonists affect the immune repertoire, while TNF-α-induced protein 3 (TNFAIP3) has a protective role against the deleterious effects of inflammation and participates in immune regulation. Objective. We investigated the immune regulation of TNFAIP3 in the pathogenesis of psoriasis and determined whether it is involved in the antipsoriatic effect of TNF-α antagonists. Methods. mRNA levels were evaluated in blood from patients with moderate-to-severe psoriasis. The effects of TNF-α antagonists were examined in a mouse imiquimod- (IMQ-) induced psoriasis-like dermatitis model. In the mouse model, TNFAIP3 mRNA expression was determined using RT-PCR. Serum levels of IL-17A, IL-23, IFN-γ, TNF-α, phosphorylated ERK1/2, p38, and JNK were measured using ELISA. The proportion of Th1 and Th17 cells in mouse spleens was analyzed using flow cytometry. Results. mRNA expression levels of TNFAIP3 in the blood were significantly lower in patients with moderate and severe psoriasis (mean±SD=0.44±0.25) compared with normal subjects (mean±SD=1.00±0.82) (P<0.01). In the mouse model, IMQ downregulated TNFAIP3 expression levels, which were increased after TNF-α antagonist treatment (P<0.05). Serum levels of Th17 cytokines (IL-17A and IL-23) and Th1 cytokines (IFN-γ and TNF-α) were significantly higher in the IMQ and IMQ/rat IgG1 groups compared with the control group, and the application of TNF-α antagonists significantly decreased the levels of inflammatory cytokines (P<0.01). Notably, phosphorylated p38 levels were increased in the IMQ and IMQ/rat IgG1 groups compared with the control group but were downregulated by treatment with TNF-α antagonists (P<0.05). Th1 and Th17 cells were significantly increased in the IMQ group compared with the control group (P<0.01). Conclusion. TNFAIP3 downregulation associated with Th1 and Th17 cell differentiation and p38 activation might contribute in part to the mechanism of immune dysfunction in psoriasis. TNF-α antagonists might partly exert their effects on psoriasis via this pathway.